Abrogation of survival disparity between Black and White individuals after the USPSTF′s 2012 prostate‐specific antigen–based prostate cancer screening recommendation. Issue 23 (5th September 2020) - Kim, Isaac E.; Jang, Thomas L.; Kim, Sinae; Modi, Parth K.; Singer, Eric A.; Elsamra, Sammy E.; Kim, Isaac Yi
Abstract : Background: In May 2012, the US Preventive Services Task Force (USPSTF) recommended against prostate‐specific antigen (PSA)–based screening for prostate cancer (PCa), assigning it a grade D. This decision then was modified in 2018 to a grade C for men aged 55 to 69 years. The authors hypothesized that changes in screening practices would reduce survival outcomes for both Black and White men but maintain racial discrepancies in outcomes. Methods: Using the Surveillance, Epidemiology, and End Results database, the authors examined PCa‐specific survival based on race and year of diagnosis. The period between January 2010 and December 2012 was categorized as the pre‐USPSTF era, whereas the period between January 2014 and December 2016 was classified as the post‐USPSTF era. The year 2013 was considered the transition year and was excluded from the analysis. Results: A total of 49, 388 men were identified in the pre‐USPSTF era who were diagnosed with PCa, approximately 83.7% of whom were White and 16.3% of whom were Black. In the post‐USPSTF era, a total of 41, 829 men were diagnosed with PCa, approximately 82.7% of whom were White and 17.3% of whom were Black. When compared with the pre‐USPSTF era, men diagnosed in the post‐USPSTF era were found to have more adverse clinical features. In the pre‐USPSTF era, White men were less likely to die of PCa than Black men. This survival disparity between White and Black men was no longer observed in the post‐USPSTF era. Conclusions: In men diagnosed with PCa between 2014 and 2016, a survival disparity between White and Black men was not observed due to a decrease in survival among White men while the survival of Black men remained steady. Abstract : After the US Preventive Services Task Force's 2012 recommendation against prostate‐specific antigen–based prostate cancer screening, survival disparities between White and Black men appear to have vanished. This observation appears to be due largely to a decrease in survival among White men whereas survival in Black men has for the most part remained steady.